1975
DOI: 10.1128/aem.30.1.72-78.1975
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Characteristics of Dungeness Crab (Cancer magister)1

Abstract: Aerobic, heterotropic microorganisms of Dungeness crab (Cancer magister) were isolated from raw crab, cooked crab, crab meats obtained during commercial processing, and from retail crab meat samples. Each microbial isolate was then identified to the genus level employing the revised replica plating procedure. Microbial groups most commonly isolated from crab meat were, in the order of predominance, Moraxella, Pseudomonas, Acinetobacter, Arthrobacter, Micrococcus, Flavobacterium-Cytophaga, and Bacillus sp. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Incubation at 20 to 25°C in the air has been used by most previous investigators to isolate and identify microorganisms from seafood (1, 2, 14). The relative numbers of the different genera found on our plates incubated under these conditions are in general agreement with previous studies (12,14). Strictly respiratory bacteria, especially Pseudomonas spp., Acinetobacter spp., and Moraxella spp., were found to predominate.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Incubation at 20 to 25°C in the air has been used by most previous investigators to isolate and identify microorganisms from seafood (1, 2, 14). The relative numbers of the different genera found on our plates incubated under these conditions are in general agreement with previous studies (12,14). Strictly respiratory bacteria, especially Pseudomonas spp., Acinetobacter spp., and Moraxella spp., were found to predominate.…”
Section: Resultssupporting
confidence: 93%
“…not complete since the microbial counts increased during MA storage, as has been reported by other investigators (1, 2, 10). The day 0 microbial flora was similar to that normally isolated from fresh marine animals (12,14,15,22).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…We have previously noted the selective elimination of Moraxella spp. from smoked salmon (7), but the opposite was observed with the cooked Dungeness crab (8).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were made by Collwell, Wicks & Tubiash (1975) and Lightner (1977) indicating that the haemolymph is not sterile and the host immune system controls low‐level bacterial infection (Brock & Lightner 1990). In contrast, others (Bang 1970; Lee & Pfeiffer 1975; Johnson 1976) have reported that the haemolymph is sterile. Previous studies with freshly caught N. norvegicus have reported the presence of Achromobacter, Acinetobacter, Cytophaga, Micrococcus, Pseudomonas, Alteromonas and Vibrio species (Cann 1970; Hobbs 1971; Montero 1998).…”
Section: Discussionmentioning
confidence: 87%